Pediatric renal lithiasis in Spain: research, diagnostic and therapeutic challenges, and perspectives - Lumbreras, Javier; Madariaga, Leire; Rodrigo, María Dolores (Frontiers in Pediatrics, 2023)
Incidence and prevalence of urolithiasis is apparently increasing worldwide, also among children and adolescents. Nevertheless, robust data have only been obtained in a few countries. In Spain, a voluntary Registry for Pediatric Renal Lithiasis has been active since 2015. Irregular participation limits its applicability, as well as its limitation to patients with a stone available for morphocompositional study, to obtain data about incidence and prevalence. On the other hand, findings about typology of stones and clinical and analytical characteristics of these subjects have been communicated in several meetings. Other valuable efforts in this field are the elaboration of guidelines for the collection and processing of urine samples for the study of urolithiasis in pediatric patients with the consensus of the Spanish Society for Pediatric Nephrology (AENP) as well as the Spanish Society for Laboratory Medicine (SEQC), the collaborative network RenalTube for the diagnosis of primary tubulopathies and the registry of patients with Primary Hyperoxaluria (OxalSpain). In many hospitals from the public healthcare system, pediatric nephrologists are the specialists in charge of the management of children with kidney stones, but there is no formal regulation on this competence. Other specialists, such as urologists, pediatric surgeons or pediatric urologists, in many cases do not offer a complete insight into the etiopathogenic mechanisms and the consequent medical treatment. Access to medication according to standards of treatment is warranted, provided a correct diagnosis is achieved, but criteria for the reimbursement of certain therapies, such as RNAi drugs for primary hyperoxaluria, are arguable.